Association of Glycemic Control with Serum Lipid Profile among the Patients of Type 2 Diabetes Mellitus in Chittagong Medical College Hospital (Bangladesh Journal of Medical Biochemistry, 2025)
Type 2 diabetic patients with poor glycemic control are more prone to dyslipidemia which has been suggested as a modifiable risk factor for the atherosclerotic macrovascular complications. Glycated hemoglobin (HbA1c) is considered as good indicator of long-term glycemic control as well as predictor of lipid profile. Early detection and treatment of lipid abnormalities can reduce the risk for cardiovascular disease in patients with type 2 diabetes mellitus (T2DM). Such type of studies in our country are limited. So we planned to evaluate the association of HbA1c with lipid profile among patients with type 2 diabetes at Chittagong Medical College Hospital, Bangladesh. This cross-sectional analytical study was carried out in the department of Biochemistry, Chittagong Medical College, Bangladesh from July 2020 to June 2021. A total 120 patients with T2DM aged 40-75 years were selected from outpatient department of Endocrinology, Chittagong Medical College Hospital by non-probability purposive sampling. Fasting blood glucose (FBG), HbA1c, fasting total cholesterol (TC), triglyceride (TG), low density lipoprotein (LDL-C), high density lipoprotein (HDL-C) were evaluated and lipid profile were compared between good glycaemic control (HbA1c